Outdoor stays—A basic human need except for older adults in residential care facilities? Researcher-practitioner interaction crosses zones and shows the way out - Nordin, Susanna; Liljegren, Madeleine; Nilsson, Martin; Bengtsson, Anna; Wijk, Helle (Frontiers in Dementia, 2024)
The aim of this discussion paper is to show the way to the outdoors by shedding light on conditions in the physical environment enabling outdoor stays for older adults living in residential care facilities (RCFs). The origin was that outdoor stays is a basic human need and applies to everyone. However, despite extensive research on the health-promoting values of contact with the outdoors, it seems that for older adults in RCFs this is not met because they often have difficulty getting outdoors on their own. Therefore, the access to and the conditions of outdoor environments are discussed and exemplified through two cases based on two evidence-based approaches, namely the principal model of four zones of contact with the outdoors, and the Swedish version of the Sheffield Care Environment Assessment Matrix (S-SCEAM). An interdisciplinary team, including both researchers and practitioners highlights future directions by showing the way to the outdoors on a national level with six suggested points. As a reader, you will gain increased knowledge about environmental qualities that support outdoor stays as well as initiatives that are needed to achieve equal conditions related to outdoor stays in RCFs.